Analisis Pemanfaatan Aplikasi Digital Dalam Pembelajaran Interperaktif Bagi Siswa Madrasah Ibtidaiyah Ibnu Aqil - S, Salman; Haekal, Ibnu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The activity of using digital applications in interactive learning for elementary school students at MI Ibnu Aqil was carried out with the aim of changing students' habits towards a more positive direction in using digital applications, and this activity is expected to be a means of introducing and learning about the use of digital applications. So that it makes the teaching and learning process in the Covid-19 era even more interactive. Considering that in the Covid19 pandemic era, the learning process for students is carried out through online media which is considered less effective and efficient. Because not everyone understands the use of technology. Based on field observations, many students already have gadgets but do not use them in the world of education. Most of them use it only as a medium of entertainment. The method of implementing this activity is done by learning by doing. With several stages, namely (1) Preparation stage, (2) Training stage, (3) Assistance stage for the learning process. The results of the MI Ibnu Aqil teacher program through the use of digital applications in interactive learning for elementary school students at MI Ibnu Aqil are considered successful in broadening the students' parents' insight even more broadly.